Efficacy of locally infiltrated tramadol compared to bupivacaine during elective ovariohysterectomy procedures in canine patients: A double-blinded randomized parallel study - James Iversen; Kieri Jermyn; Emily Dockray; Michelle Eastwood; Randi Rotne (Research in Veterinary Science, 2025)

Assessing colostral and serum immunoglobulin G in alpacas using Brix refractometry and total serum protein - Amber K. O’Neill; Christopher E. Petzel; Joanne H. Connolly; Jane L. Vaughan; Randi Rotne (Veterinary Research Communications, 2024)
The adequate transfer of passive immunity is a critical factor in neonatal development and survivability. Although well documented in the dairy and equine industries, the recognition of inadequate immunoglobulin transfer on-farm and its impact on the ability of alpaca cria to thrive is largely unknown. Colostrum samples were collected from female alpaca within 24 h of parturition by the owners and whole blood collected from cria by the investigators between 1 and 7 days of age. Direct IgG concentration of milk and serum was determined using radial immunodiffusion assay (RID) and was indirectly estimated using optical and digital Brix refractometry for total solids and clinical refractometry for total serum protein. There was a strong correlation between optical and digital Brix refractometry, and colostral IgG concentration determined by RID. There was a moderate correlation between serum IgG concentration determined by RID and total serum protein in crias. Optical and digital Brix refractometry for colostral IgG estimation and total serum protein for serum IgG estimation are reliable, accurate and easy-to-use tools that can be used on-farm by trained, competent technicians to assess a failure of passive transfer in alpacas. A pilot study at one property only was performed, due to COVID-19 travel restriction interference. Further research is required to determine the reference intervals for these tools to be practical.